2022
DOI: 10.47542/sauied.1170255
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Financial Performance of Food Sector Businesses Listed on Borsa İstanbul in the COVID-19 Pandemic with Gray Relational Analysis Method

Abstract: 2019 yılında başlayan ve ardından dünya çapında bir salgın olan COVID-19, küresel anlamda hem ekonomik hem de sosyal açıdan negatif sonuçlar oluşturmuştur. Yaşanan bu gelişmelerden hemen hemen her sektör etkilenmiş olup, Gıda, İçecek ve Tütün Sektörü de bu sektörler arasında yer almaktadır. Çalışma ile ulaşılmaya çalışılan, yaşanan gelişmelerin beraberinde Borsa İstanbul (BİST)’a bağlı Gıda, İçecek ve Tütün Sektöründe yer alan şirketlerin, COVID-19 pandemi dönemini kapsayan 2019-2021 yıllarında nasıl etkilendi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Mızrakçı concluded that both the rent and the size of the sales area were significant criteria affecting performance (Mızrakçı, 2023). Bozkır, Yıldız, and Türkmen (2022) acknowledged that the COVID-19 pandemic brought about numerous economic and social challenges. Their study specifically explored the pandemic's impact on the food, beverage, and tobacco sector.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Mızrakçı concluded that both the rent and the size of the sales area were significant criteria affecting performance (Mızrakçı, 2023). Bozkır, Yıldız, and Türkmen (2022) acknowledged that the COVID-19 pandemic brought about numerous economic and social challenges. Their study specifically explored the pandemic's impact on the food, beverage, and tobacco sector.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The researchers calculated seven ratios and employed the GRI relational analysis method. The findings indicated that certain companies were able to leverage the pandemic circumstances to their advantage, while others encountered difficulties in adapting to the changing conditions (Bozkır, Yıldız, & Türkmen, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%